2020
DOI: 10.1016/j.asjsur.2020.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Complicated appendicitis are common during the epidemic period of 2019 novel coronavirus (2019-nCoV)

Abstract: Objectives To assess the prevalence of complicated appendicitis (including gangrene, abscess and perforation) after the outbreak of the 2019-nCoV epidemic and to identify the risk factors associated with complicated appendicitis. Methods Two groups were established in the study consisting of: one group for cases of acute appendicitis before the 2019-nCoV epidemic (before January 1, 2020; pre-epidemic group) and another group for those after the epidemic outbreak (after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
56
5
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 12 publications
6
56
5
3
Order By: Relevance
“…[ 22 , 23 ] It is precisely in our study that during the epidemic period, the time interval from the onset of symptoms to medical treatment in patients with acute appendicitis was significantly prolonged, while the proportion of patients with suppurative appendicitis was higher, and the incidence of complex appendicitis was also higher. It has also been reported that the perforation rate of acute appendicitis in children increased during the epidemic, [ 7 ] and the incidence of complex appendicitis increased in the United States and other areas, [ 24 , 25 ] which is consistent with our research results.…”
Section: Discussionsupporting
confidence: 93%
“…[ 22 , 23 ] It is precisely in our study that during the epidemic period, the time interval from the onset of symptoms to medical treatment in patients with acute appendicitis was significantly prolonged, while the proportion of patients with suppurative appendicitis was higher, and the incidence of complex appendicitis was also higher. It has also been reported that the perforation rate of acute appendicitis in children increased during the epidemic, [ 7 ] and the incidence of complex appendicitis increased in the United States and other areas, [ 24 , 25 ] which is consistent with our research results.…”
Section: Discussionsupporting
confidence: 93%
“…Concern has been raised that patients are presenting with increased disease severity in the COVID‐19 threatened climate. Literature from the UK, China, Spain, Australia and Colombia has shown increased severity of appendicitis in patients presenting in the COVID‐19 era compared to prior 12,19–22 . This study did not demonstrate an increased severity in patients presenting with diverticulitis, appendicitis or pancreatitis.…”
Section: Discussioncontrasting
confidence: 66%
“…However, the usually low rate of very complicated cases of appendicitis does not allow an uncritical extrapolation of the current results to other surgical emergencies. A comparison with the international literature shows some parallels regarding a reduction in appendectomies [ 13 , 14 ], a later presentation, and an increased inflammatory reaction [ 5 , 15 – 18 , 20 , 31 ]. The international survey of Ielpo et al of more than 700 surgeons worldwide reported a decrease of appendicitis and an increase of complicated cases based on a questionnaire [ 20 ].…”
Section: Discussionmentioning
confidence: 99%